Advancing critical race pedagogical approaches in social work education. Issue 3 (3rd September 2022) - Duhaney, Patrina; Lorenzetti, Liza; Kusari, Kaltrina; Han, Emily
ABSTRACT: The recent COVID-19 pandemic drew a sharp focus on existing inequities for racialized communities in Canada and globally. A paucity of research-informed transformative learning models in social work has resulted in the persistent centering of Western ways of knowing. Current efforts do not adequately address the nuances of systemic and structural racial inequities, leaving students unprepared to deal with these issues in the classroom and in practice. We propose critical race pedagogy as an essential framework to promote and enrich social work learning environments where students can engage in courageous conversations about race, racism, power and oppression.